Las relaciones económicas entre Angola y China (2000-2014) - Ricardo Ouriques, Helton; Nunes De Avelar, Amanda Caroline (El Colegio de México, 2017)
The aim is to discuss economic relations between China and Angola since the 2000s to demonstrate that economic ties between the two countries have deepened in the changing context of Chinese political economy, which has resulted in a search for strategic resources in order to maintain it’s model of economic growth. We attempt to understand whether this increased economic rapprochement can change the Angolan peripheral position in the global economy; we conclude that the current situation does not represent sufficient conditions for a structural change in the position of Angola in the capitalist world-economy.